Examination of the importance of anger/irritability and limited prosocial emotion/callous-unemotional traits to understand externalizing symptoms and adjustment problems in adolescence: A 10-year longitudinal study - Urben, Sébastien; Habersaat, Stéphanie; Palix, Julie; Fegert, Jörg M.; Schmeck, Klaus; Bürgin, David; Seker, Süheyla; Boonmann, Cyril; Schmid, Marc (Frontiers in Psychiatry, 2022)
Objective Within a longitudinal study (10-year follow-up), we aim to examine the role of anger/irritability and limited prosocial emotion/callous-unemotional traits in predicting externalizing symptoms and adjustment problems in individuals formerly in youth residential care institutions. Method These dimensions were assessed in 203 young adults, with baseline assessments during youth residential care and a follow-up 10 years later. Results In general, emotional problems and psychopathological symptoms did not reduce over time. Analyses of regression revealed that a younger age at baseline, anger/irritability both at baseline assessment, and regarding their aggravation over time refer to significant predictors of the level of externalizing symptoms at 10-year follow-up (R2 = 0.431) and the worsening of externalizing symptoms over time (R2 = 0.638). Anger/irritability has been observed to be a significant predictors of both the level of adjustment problems at 10-year follow-up (R2 = 0.471) and its worsening over time (R2 = 0.656). Discussion Our results suggest that dysregulation of anger/irritability is a key factor in the prediction of long-term externalizing symptoms and adjustment problems as well as its worsening over time. Possible implications for intervention and prevention are discussed.